The Influence of Changing Belt Loading Conditions on the Operational Condition of the Belt Transmission - Jozef Mascenik; Tomas Coranic (Actuators)
Given the fact that belt drives are used to transmit power to a fairly large extent, it is natural to devote scientific attention to their transmission with an effort to contribute to the constant technical and technological progress in the field of belt production and use. For testing and monitoring belt drives, a measuring system was designed and manufactured, which allowed the installation of various types of belt drives and, under a controlled load, to monitor selected parameters and the behavior of individual transmission elements. The presented contribution presents both the measuring system itself and experimental measurements on three V-belts of the same size manufactured by three different manufacturers. During the experimental measurements, parameters such as belt tension were changed by changing the axial distances of the pulley axes; by connecting electric motors through frequency converters, it was possible to control the change in the input speed of the transmission and, at the same time, the load on the output pulley. On the proposed specific design solution for testing belt drives, the actual speed of the input and output pulleys was measured by sensors to determine the belt slip, and the belt’s floating in one plane was monitored using high-precision distance measurement sensors. The analysis of the belt drives also included an assessment of their impact on other parts of the machine or equipment (for example, when transmitting large forces, this can have a negative impact on bearings and gearbox components) on which they are installed; therefore, vibration measurements were also performed. The results of the experimental measurements can contribute to designers choosing a belt drive, for example, even under boundary load parameters and extreme conditions.